(3GdeNJUQ GdeajO aj Yde GdJGQjNs - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdCQV hGdSeGA heG ajgG YHQI dChdi Gdfgi s
(3BNQgG (B:s
(3hcGf Pdc hbJ GdVMi ai jhe GdKdGKGA KGef ef TgQ QLH GdCUe SfI SHY hSJjf hKeGfeGFI hMSHfG Gddg hfYe Gdhcjd s
(3GfXQ Qbe (B458 (3Qbe (B1219 (3JGQjNs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B150s
Keywords: (3GdJGQjNs